The Influence of Educational Media on Sleep Quality and Work Fatigue in Workers - Pratopo, Julinda Zahrani; Kurniasari, Ratih; Andriani, Eka (Universitas Ibn Khaldun Bogor, 2025)
Sleep health is important for the overall health and quality of life of workers. Workers with sleep disorders experience various physical and mental health problems, including abnormal vital signs, mood disorders, poor quality of life, frequent workplace injuries, and even premature death. The main objective of this study is to determine the effect of educational media on sleep quality and work fatigue in workers. This study uses a Quasi Experimental research form. With a design using a Pre-Post Test Design. The sample in this study were employees at Konveksi Elnino and PT. X which is engaged in paper manufacturing with a total of 36 respondents. The results of the study on 36 respondents showed that the age of respondents ranged from 23-32 years as many as 20 respondents (55.35%) and 33-49 years as many as 16 respondents (44.65%). Workers aged 15-64 years are included in productive age workers, who are considered capable of producing goods and services in the production process. Productive age can affect worker performance because with increasing age, the degenerative process in body organs decreases so that workers are more easily tired. Based on statistical tests, there was an increase in knowledge and attitudes in Calendar Media (2D) and Hand Fan Media (Innovation), while in Youtube Video Shorts Media (3D), there was no increase in knowledge and attitudes.